SOLUTIONS TO SOME PROBLEMS IN MATHEMATICS THAT CAN BE SOLVED IN A SPECIAL WAY - Makhmudov Aʼzam Kudratovich; Mamaraimov Bekzod Kadirovich; Musurmonov Ma'ruf Akromovich (Journals Park Publishing, 2025)
Mathematics is a broad field filled with problems that can often be solved using diverse methods. However, certain problems possess unique or special solving techniques that make them particularly intriguing. These problems often lead to elegant solutions that are not immediately apparent through conventional methods. This article explores various mathematical problems that can be solved in such a "special" way, highlighting the creativity, insight, and innovation involved in their resolution. The solutions presented here offer deeper insights into mathematical theory and are representative of the elegance that can arise when mathematical thinking is pushed to its boundaries. Through analysis and examples, this article illustrates how problems that initially appear complex can sometimes be simplified through clever and unconventional approaches.
Keywords: Special methods, mathematical problems, creative solutions, mathematical theory, problem-solving techniques.